Hybrid LEDs based on ZnO nanowire structures. (October 2017) - Voss, Tobias; Waldvogel, Siegfried R.
Abstract: This paper summarized the research, development, and state of the art of hybrid ZnO nanowire LEDs, in which electroluminescence is generated at the junction between n-type doped ZnO nanowire structures and specific p-type doped polymers (in particular PEDOT, PEDOT:PSS, or PFO). Different device architectures will be reviewed and discussed with a particular emphasis on the electronic transport through the hybrid structures and the microscopic processes of light emission. Finally, a gas-phase deposition technique for conductive polymers will be presented which might help improve the performance of hybrid ZnO nanowire LEDs in the future.